Study of the nucleolar cycle and ribosomal RNA distribution during meiosis in triatomines (Triatominae, Heteroptera) - Morielle-Souza, Alessandra [UNESP]; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Aspects of nucleolar activity during spermatogenesis were assessed in three triatomine species (Panstrongylus inegistus, Rhodnius pallescens and Triatoma infestans) using cytochemical and fluorescent staining techniques. Toluidine blue and a variant of critical electrolytic concentration (CEC) allowed the discrimination of rRNA providing structural details of the nucleolus and RNA distribution during meiotic cell division. Acridine orange fluorochrome staining permitted the differentiation of nucleic acids, and silver-ion impregnation made possible the observation of prenucleolar bodies (PNBs). Our results support the phenomenon known as "persistence of the nucleolar material", and the hypothesis of post-meiotic reactivation of rRNA genes. Nucleolar organizer regions (NORs) were observed in some metaphasic spermatogonial chromosomes in P. inegistus and T infestans. In P. inegistus at diplotene-diakinesis, NORs were also detected in one of the sex chromosomes and in an autosome. Therefore, it may be inferred that, in triatomines, the nucleolus does not completely disappear, but persists in the form of small bodies that get together to form the next nucleolar cycle which, in the case of meiosis, will be completed if fertilization occurs and a new zygote is formed. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Nucleolus; NORs; PNBs; Spermatogenesis; Panstrongylus inegistus; Rhodnius pallescens; Triatoma infestans